Performance of broiler chickens fed bush marigold (Aspilia Africana) leaf extract - Uchewa, E.N.; Amaduruonye, W.; Onunkwo, D. N.; Njoku, H. A. (Nigerian Journal of Animal Science, 2023)
The effect of Aspilia africana (bush marigold) leaf extract on the performance of broiler chickens in a feeding trial lasting eight weeks was studied. A total of one hundred and twenty (120) day-old Arbor acre broiler chicks were randomly grouped into four treatments with three replicates containing ten birds per replicate in a completely randomized design (CRD). The Aspilia africana leaves were collected around the premises of Ebonyi State University Teaching and Research Farm, they were detached from the stem, sun dried and ground into fine powder. 5g of the powdered Aspilia africana was dissolved in 1 liter of warm water for the period of four (4) hours on daily basis and the extract was used for the research, T1 served as control that is no extract in their drinking water of 2 liters, T2 receive 150ml/2liters of water, T3 received 200ml/2liters of water while T4 received 250ml/2liters of water on daily basis for 8 weeks. Growth parameters measured were weight gain, feed intake, water intake and feed conversion ratio. The result showed that there are significant differences (P<0.05) in body weight gain, daily feed intake, daily water intake, feed conversion ratio while there were no significant differences in the daily weight gain and final body gain. T4 showed the highest value when compared to T2 and T3. In conclusion, 250ml/2liters of water of Aspilia africana leaf extract can serve as a growth promoter hence recommended for broiler production.